The Effect of Bruton’s Tyrosine Kinase (BTK) Inhibitor in the Eosinophilic Asthma Model of Mouse - 최예지 (The Graduate School, Ajou University, 2024)
Background Bruton’s Tyrosine kinase (BTK) plays a pivotal role as the key mediator in B cell receptor signaling. Recent research has revealed that it is also expressed in cells critical to asthma development, such as T cells, and eosinophils. This study aims to investigate the potential of BTK inhibitor, ibrutinib, in eosinophilic asthma mouse model. Methods BALB/c mice were sensitized with OVA via intraperitoneal injections and followed by OVA nebulizations. The mice were treated with 250ug/ml or 500ug/ml of ibrutinib before the second intraperitoneal injection and the first challenge. Two days after the last OVA challenge, airway hyperresponsiveness (AHR) was assessed with methacholine, and differential cell count in bronchoalveolar lavage fluid (BALF) was performed. The cytokines were measured in BALF, and serum OVA-specific IgE and IgG antibody levels were evaluated by ELISA. The inhibitory effect of ibrutinib was also evaluated in splenic mononuclear cells, mast cells, eosinophils, and T cells in vitro. Results Treatment with ibrutinib significantly attenuated AHR and airway inflammation, compared to the positive control. The treatment also reduced cytokine levels and suppressed OVA-specific IgE and IgG production, especially in the group treated before OVA sensitization, compared to the positive control. Additionally, ibrutinib decreased beta-hexosaminidase release from mast cells, type 2 cytokine production from mononuclear cells and T cells, and eosinophilic activation markers in vitro. Conclusion The results of this study suggest that ibrutinib treatment could exert anti- allergic effects by inactivating B cells and other BTK-expressing cells. Further studies are needed to investigate the potential therapeutic effect of ibrutinib on allergic diseases.
학위논문(석사)--의생명과학과,2024. 2
Keywords: Asthma; Bruton's Tyrosine kinase; Eosinophil; Mast cell; T cell